Fluorometric fiber optic drop sensor for atmospheric hydrogen sulfide - Cardoso, A. A.; Liu, H. H.; Dasgupta, P. K. (Elsevier B.V., 1997)
A fluorometric technique based on a liquid drop excited from its interior by an optical fiber is described for the measurement of low concentrations of atmospheric hydrogen sulfide (H2S). A drop of alkaline fluorescein mercuric acetate (FMA) solution is suspended in a flowing air sample stream and serves as a renewable sensor. An optical fiber contained within the conduit that forms the drop, brings in the excitation beam; the fluorescence emission is measured by an inexpensive photodiode positioned close to the drop. As H2S in the sample is collected by the alkaline drop, it reacts rapidly with FMA resulting in a significant decrease in fluorescence intensity, proportional to the concentration of H2S sampled. The chemistry of this uniquely selective reaction has been well established for many years, the present technique permits a simple fast inexpensive near real-time measurement with very little reagent consumption. Even without prolonged sampling/preconcentration steps, limits of detection (LODs) in the double digit ppbv range is readily attainable. (C) 1997 Elsevier B.V. B.V.
Keywords: FMA; H2S; limit of detection; optical fiber